2022
DOI: 10.3389/fitd.2021.789273
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Aedes Mosquito Breeding Habitats in Suburban and Urban Areas of Kinshasa, Democratic Republic of the Congo

Abstract: BackgroundThe knowledge of key elements of the ecosystem affecting mosquito distribution and their population dynamics is essential for designing mosquito-borne disease interventions. The present study characterized the physicochemical properties of Aedes mosquito breeding habitats in Democratic Republic of the Congo.MethodsA cross-sectional survey was carried out in Kinshasa, from February to April 2021. The physicochemical characteristics of the natural and artificial aquatic habitats of Aedes were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
1
6
2
3
Order By: Relevance
“…Although previous studies had specified that TDS levels of Aedes breeding habitats are low [ 27 , 46 – 48 ], our results revealed that dengue vectors can survive in a broad range of TDS and the level of TDS positively correlates with BPR of Ae. aegypti and Ae.…”
Section: Discussioncontrasting
confidence: 83%
“…Although previous studies had specified that TDS levels of Aedes breeding habitats are low [ 27 , 46 – 48 ], our results revealed that dengue vectors can survive in a broad range of TDS and the level of TDS positively correlates with BPR of Ae. aegypti and Ae.…”
Section: Discussioncontrasting
confidence: 83%
“…The occurrence of mosquito larvae in breeding sites was affected by some factors, including the water's salinity, DO, temperature, pH, and turbidity. They had a substantial impact on the Aedes breeding sites and mosquito density (Mbanzulu et al 2022). These water parameters have an impact on some fundamental mosquito traits, including survival, body size, and biting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Analisis data menunjukkan nilai p>0,05, menunjukkan bahwa tidak ada hubungan yang signifikan secara statistik antara jumlah larva nyamuk dan suhu lokal di TWA X. Penelitian terakhir menunjukkan bahwa larva Aedes aegypti tidak berkorelasi dengan suhu di Kota Zanzibar, Tanzania, dan Kota Bandung, Jawa Barat (Saleh et al, 2018;Sarwita et al, 2018) Di sisi lain, Mbanzulu et al (2022) mengidentifikasi hubungan antara pH dan suhu terhadap jumlah larva nyamuk (Mbanzulu et al, 2022).…”
Section: Pembahasanunclassified
“…Dari kisaran jumlah tersebut, banyak larva nyamuk berada pada pH optimal untuk bereproduksi. Hal ini sesuai dengan penelitian Mbanzulu et al (2022) pada Aedes di Congo yang menemukan korelasi positif dengan jumlah larva Aedes (Mbanzulu et al, 2022). Namun sebaliknya, penelitian yang dilakukan oleh Suyaningtyas et al (2017) tidak menunjukkan adanya korelasi antara pH dan jumlah larva (Suryaningtyas et al, 2017).…”
Section: Pembahasanunclassified
See 1 more Smart Citation